Pollinator mediated selection in Pelargonium reniforme Curtis (Geraniaceae) : patterns and process - De Wet, Leigh-Ann Robynne (Rhodes University, Faculty of Science, Botany Department)
Pelargonium reniforme is currently divided into two subspecies, P. reniforme subsp. reniforme and P. reniforme subsp. velutinum. The species falls into section Reniformia along with the closely-related P. sidoides. Observations of the section showed some discrepancies in the current taxonomy; mainly floral variation that was not recorded in the descriptions of the subspecies of P. reniforme, particularly the differences in hypanthium lengths. Patterns of variability were analysed using both morphometrics and inter simple sequence repeat (ISSR) data for P. reniforme (both subspecies), and P. sidoides. Results showed no support for the current subspecific division of P. reniforme but also no support for the current status of P. sidoides as a separate species. However, both morphometric and ISSR data show some evidence for the existence of two distinctly separate groups within P. reniforl1le subsp. velutinum as two distinct types have been recognized: those with bright pink flowers with long tubes (up to 70mm), and those with pale pink flowers with shorter tubes (as little as 8mm). These two forms have been found in a single population (Grahamstown), where they occur sympatrically, as well as in monomorphic populations. Analyses of the processes thought to be responsible for the observed patterns were conducted on the Grahamstown population. Observations of pollinators suggest that long-tongued insects (Butterflies, Nemestrinid flies) pollinate the long-tubed flowers and short-tongued insects (Bombyliid flies, long-tongued bees) pollinate short-tubed flowers. However, analysis of selection gradients in the population, indicate no directional selection is occurring for hypanthium lengths. The results of this thesis show that selection is occurring within Pelargonium reniforme, but at this time, selection is not strongly directional and floral differences are maintained, even when floral forms occur sympatrically. It is suggested that a review of the taxonomy be undertaken as well as additional pollination and selection studies to confirm suspected taxonomic groupings and relationships between the floral forms respectively.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Pelargoniums -- Classification; Pelargoniums -- Pollen; Pelargoniums -- Selection